Asphalt Concrete Mixture Innovation Using Styrofoam Waste - M. Reza Hasrul; Moh. Junaedi Rahman; Ahmad Rifqi Asrib (Newinera Publisher, 2021)
The purpose of this research is to determine the properties of an AC-BC concrete asphalt mixture with additional Styrofoam waste to bitumen. This study was conducted fully at the State University of Makassar's Laboratory of Materials Testing. The amount of Styrofoam utilized in this investigation was 6 percent, 8 percent, 10 percent, and 12 percent of the total weight of KAO asphalt (Optimum Asphalt Weight). This study used a total of 15 specimens, with 5 being used to determine KAO and 12 being used following KAO. The Marshall method was utilized, which involved immersing the test object in a water bath at 60 degrees Celsius for 30 minutes. Density, stability, flow, Marshall Quotient (MQ), VIM, VFA, and VMA were all determined using the Marshall test. The General Bina Marga 2018 specification revision 3 was utilized as a guideline. The findings of this investigation show that the asphalt penetration value falls as styrofoam material increases. Stability values in the additions of 6 percent and 8 percent, MQ values at 6 percent, VIM 12 percent, and VFA 6 percent do not satisfy criteria, while density values, flow, and VMA in all variations of styrofoam addition meet the General Bina Marga specifications in 2018 refisi 3. Based on the results of the Marshall test with an Optimal Asphalt Content (KAO) of 5.7 percent, this research suggests that a percentage substitution of 10% can be employed to get positive outcomes.